Layer-specific strain in patients with cardiac amyloidosis using tissue tracking MR - Li, Zheng; Yan, Cheng; Hu, Guo-Xiang; Zhao, Rui; Jin, Hang; Yun, Hong; Wei, Zheng; Pan, Cui-Zhen; Shu, Xian-Hong; Zeng, Meng-Su (Frontiers in Radiology, 2023)
Background: Cardiac infiltration is the major predictor of poor prognosis in patients with systemic amyloidosis, thus it becomes of great importance to evaluate cardiac involvement.Purpose: To evaluate left ventricular myocardial deformation alteration in patients with cardiac amyloidosis (CA) using layer-specific tissue tracking MR.Material and Methods: Thirty-nine patients with CA were enrolled. Thirty-nine normal controls were also recruited. Layer-specific tissue tracking analysis was done based on cine MR images.Results: Compared with control group, a significant reduction in LV whole layer strain values (GLS, GCS, GRS), as well as layer-specific strain values, was found in patients with CA (all P < 0.01). In addition, GRS ,GLS, as well as subendocardial and subepicardial GLS, GRS and GCS, were all diminished in patients with CA and reduced LVEF, when compared to those with preserved or mid-range LVEF(all P < 0.05). GCS showed largest AUC(0.9952, P=0.0001) with sensitivity 93.1% and specificity 90%) to predict reduced LVEF(<40%). Moreover, GCS was the only independent predictors of LV systolic dysfunction, (Odds Ratio:3.30, 95% CI:1.341-8.12, P=0.009).Layer-specific tissue tracking MR could be a useful method to assess left ventricular myocardial deformation in patients with CA.